O Instituto Federal do Tocantins e a formação de professores: caminhos, contradições e possibilidades - Oliveira, Denise Lima de (2019)
This thesis analyzes the political assumptions guiding the conception of teacher formation at the Instituto Federal do Tocantins [Federal Institute of Tocantins]. The research focuses on the contradictions arising from the implementation of licentiate (undergraduate) courses in this institution, during the expansion of the Rede Federal de Educação Profissional [Federal Network of Professional Education] and the creation of Federal Institutes itself. Teacher training at FIs was imposed by Law 11,892/2008, which created these institutions and determined that 20% of their undergraduate vacancies must be reserved for licenciate and/or special programs of pedagogic training. The law also determined that priority should be given to Science, Mathematics, and teacher training for professional education. In this investigation, we study the licentiate course in Mathematics, created at the Palmas campus in the second half of 2009, shortly after the begining of the transition process. Several research procedures were adopted, such as: literature review on the theme and its correlated subjects; extensive documentary research of the regulatory bodies of education, including those elaborated within the Federal Network, the IFTO and the Mathematics course itself; semi-structured interviews with the managing officers of the institution; and a questionnaire for the Mathematics students. We conclude that FIs have assumed a strategic role in the wider scenario of higher education policies, contributing to the democratization of this level of education, especially by diversifying the course offer, and also acquired relevance among the several advances in expansion and democratization of higher education achieved by the Lula and Dilma administrations. However, these policies were tainted by contradictions caused by the lack of time to reflect on the new institutionally and its processes of course creation, especially licentiate degrees, an issue that originated from the growth of the Federal Network itself. In this context, institutions recurred to pre-existing facilities and focused on areas with a larger number of teachers to facilitate the offer. The research shows that licentiate courses predominate in the offer of higher education by the IFTO, but this does not represent a clear institutional commitment to teacher training, since the analyzed documents did not refer to the policy of teacher training practiced at the institution nor to the conception of teacher training of its undergraduate courses. However, the thesis recognizes the strategic role that the institution occupies in the state of Tocantins, both for its territorial reach and for guaranteeing access to basic and higher education with good quality standards.